Initial-boundary problems for systems of a high order doubly nonlinear parabolic equations with variable exponent of nonlinearity - T. M. Bokalo (Математичні Студії, 2012)
Consider a mixed problem for a class of system of a high order doubly nonlinear parabolic equations with variable exponent of nonlinearity. This problem is considered in generalized Lebesgue-Sobolev spaces. As a result, we reached a condition of the existence of a solution. We use here Galerkin's procedure.